Pelaksanaan Pembelajaran Seni Budaya (Musik) Tradisional Gandang Tambua Di MTSN 4 Padang Pariaman - Miki Padreawan; Marzam Marzam (FBS Universitas Negeri Padang, 2020)
This research aims to describe the implementation of cultural arts learning (music) of traditional gandang tambua in Mts Negeri 4 Padang Pariaman in which the game of gandang tambua in madrasah is an implementation of the local content curriculum used by madrasah in the curriculum 2013. The research method was qualitative research with using a descriptive analysis research approach. The object of research was the learning activity of Tambua traditional music which was carried out at class VIII-1 both of theory and practice learning. The research instruments used were observation, interviews, and documentation studies. Techniques of data collection were done by taking documentation notes, field notes and interviews guideline. The results of the study explain that the implementation of cultural art learning (music) of the gandang tambua in MTs Negeri 4 Padang Pariaman still uses the usual or conventional methods. The use of lecture, question and answer, discussion and training methods by imitating the game gandang tambua that the teacher always demonstrates is applied in theory and practice learning activities. Besides that, in the training activityof gandang tambua, the teacher introduces the activitiy of imitating, remembering and memorizing the model of the punch that the teacher demonstrates. These learning ways raise variety of problems in practice, especially when explaining and practicing the gandang tambua in front of the students, the teacher does not look for methods that are suitable and also the teacher does not use adequate learning media.